Curcumin improves high glucose-induced INS-1 cell insulin resistance via activation of insulin signaling. Issue 2 (4th December 2014) - Song, Zhenfeng; Wang, Huan; Zhu, Lin; Han, Mingbao; Gao, Yuan; Du, Yu; Wen, Ying
Abstract : INS-1 cells were induced by high glucose into insulin resistance. Curcumin effectively increased glucose stimulated insulin secretion. Abstract : Curcumin is a yellow pigment isolated from Corcuma longan. This research investigates the improvement of curcumin on INS-1 cells with insulin resistance induced by high glucose. INS-1 cells were treated with high glucose (30 mmol L −1 ) for 48 h. Subsequently, the medium was replaced with curcumin for 24 h. Curcumin effectively increased insulin gene expression and glucose stimulated insulin secretion (GSIS) in a dose-dependent manner. Furthermore, the molecular mechanism of curcumin-induced insulin expression and secretion in high glucose-induced INS-1 cells was investigated in this study. Curcumin increased the expression of glucose transporter 2 (GLUT2) and phosphorylation of insulin receptor (IR), insulin receptor substrate-1 (IRS1), phosphatidylinositol-3-kinase (PI3K) and AKT in the INS-1 cells. Moreover, curcumin stimulation increased the expression of PDX-1 and GCK. This investigation suggests that curcumin prevented high glucose-reduced insulin expression and secretion through activation of the PI3K/Akt/GLUT2 pathway in INS-1 cells.